Multiple gene-deletion vaccinia virus Tiantan strain against mpox - Yilong Zhu; Dapeng Li; Renshuang Zhao; Minghua Chen; Yue Li; Xia Yang; Hongyue Mao; Xiao Li; Yiquan Li; Chao Shang; Xianzhu Xia (Virology Journal)
Abstract Monkeypox virus (MPXV) is an important zoonotic pathogenic virus, which poses serious threats to public health. MPXV infection can be prevented by immunization against the variola virus. Because of the safety risks and side effects of vaccination with live vaccinia virus (VACV) strain Tian Tan (VTT), we constructed two gene-deleted VTT recombinants (TTVAC7 and TTVC5). The immunogenicity and protective effects of the gene-deleted VTT vaccine were assessed using BALB/C mice challenged with VTT and New Zealand rabbits challenged with MPXV. The results demonstrated strong humoral and cellular immune responses. The VTT-specific and neutralizing antibody titers, specific T cell levels, and degree of dendritic cell maturation of the mice, in addition to the MPXV neutralizing antibody titers and IFN-γ, IL-6, and TNF-α levels of the rabbits were markedly higher in the groups immunized with TTVAC7 and TTVC5 than the control groups (p < 0.05). Moreover, immunization with TTVAC7 and TTVC5 reduced morbidities caused by VACV and MPXV infection. The weight change, lung histological score, and residual virus of the mouse model (p < 0.05). Similarly, the temperature change, pock number, lung histological score, and residual virus of the rabbit model were significantly reduced in the groups immunized with TTVAC7 and TTVC5 (p < 0.05). Collectively, these results demonstrate that TTVAC7 and TTVC5 may be used as potential live attenuated vaccines against MPXV infection.